Remote vs. conventional navigation for catheter ablation of atrial fibrillation: insights from prospective registry data - Bruck, Jan-Hendrik van den; Thomas, Dierk (Clinical research in cardiology, 2019)
BackgroundRobotic (RNS) or magnetic navigation systems (MNS) are available for remotely performed catheter ablation for atrial fibrillation (AF).ObjectiveThe present study compares remotely assisted catheter navigation (RAN) to standard manual navigation (SMN) and both systems amongst each other.MethodsThe analysis is based on a sub-cohort enrolled by five hospitals from the multicenter German ablation Registry.ResultsOut of 2442 patients receiving catheter ablation of AF, 267 (age 61.4 ± 10.4, 69.7% male) were treated using RAN (RNS n = 187, 7.7% vs. MNS n = 80, 3.3%). Fluoroscopy time [RNS median 17 (IQR 12-25) min vs. MNS 22 (16-32) min; p < 0.001] and procedure duration [RNS 180 (145-220) min vs. MNS 265 (210-305) min; p < 0.001] were significantly different. Comparing RAN (11%) to SMN (89%) fluoroscopy time (RAN 19 (13-27) min, vs. SMN 25 (16-40) min; p < 0.001), energy delivery (RAN 3168 (2280-3840) s vs. SMN 2640 (IQR 1799-3900) s; p = 0.008) and procedure duration [RAN 195 (150-255) min vs. SMN 150 (120-150) min; p = 0.001] differed significantly. In terms of acute and 12 months outcome, no differences were seen between the two systems or in comparison to SMN.ConclusionAF ablation can be performed safely, with high acute success rates using RAN. RNS results in less fluoroscopy burden and shorter procedure durations. Compared to SMN, a reduced fluoroscopy burden, prolonged procedure and ablation duration were observed using RAN. Overall, the number of RAN procedures is small suggesting low impact on clinical routine of AF ablation.
Published online: 29 August 2018
Gesehen am 11.09.2019